Nubian Levallois reduction strategies in the Tankwa Karoo, South Africa - Hallinan, Emily (2021)
The Middle Stone Age record in southern Africa is recognising increasing diversity in lithic technologies as research expands beyond the coastal-montane zone. New research in the arid Tankwa Karoo region of the South African interior has revealed a rich surface artefact record including a novel method of point production, recognised as Nubian Levallois technology in Late Pleistocene North Africa, Arabia and the Levant. We analyse 121 Nubian cores and associated points from the surface site Tweefontein against the strict criteria which are used to define Nubian technology elsewhere. The co-occurrence of typically post-Howiesons Poort unifacial points suggests an MIS 3 age. We propose that the occurrence of this distinctive technology at numerous localities in the Tankwa Karoo region reflects an environment-specific adaptation in line with technological regionalisation seen more widely in MIS 3. The arid setting of these assemblages in the Tankwa Karoo compares with the desert context of Nubian technology globally, consistent with convergent evolution in our case. The South African evidence contributes an alternative perspective on Nubian technology removed from the 'dispersal' or 'diffusion' scenarios of the debate surrounding its origin and spread within and out of Africa.